Retrospectives on Turkish Studies in Canada - Ahmet Murat Kadıoğu; Çağatay Benhür (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
Howard A.Reed in 1997, “Turkish Studies in North America” has informed the public by publishing this article. After more than 15 years of this study, making it a bit more specific, we refer to the work done Turcology in Canadian universities today. We have also added an element of comparison in terms of Canadian studies and documents about the Turkish Republic in the university archives. Between the years 1914-1947 a thesis information Turcology made in the areas of Canadian universities are absent, at McGill University in 1948, When examining the period 1948 to the present day;T.L.B. O'Neill's work began with data entry. Canada is working with insufficient Turcology studies but gradual increase shows that it is possible to have a bigger research one day.